2009
DOI: 10.1111/j.1601-0825.2009.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Association among interleukin‐6 gene polymorphism, diabetes and periodontitis in a Chinese population

Abstract: The IL-6-572 genotype and allele distributions are unique to subjects with CP&T2DM in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 36 publications
1
36
0
10
Order By: Relevance
“…Most studies demonstrated that the IL-6 gene −572 G allele was associated with an increased risk of T2DM (Deng et al, 2004;Hamid et al, 2005;An et al, 2007;Koh et al, 2009;Tang et al, 2010;Wang et al, 2010). However, several other studies showed that there was no significant association between the IL-6 gene −572 C/G polymorphism and T2DM risk (Kitamura et al, 2002;Xiao et al, 2009;Zhang et al, 2011). A previous meta-analysis showed that the IL-6 gene -174 G/C polymorphism was not associated with T2DM risk (Qi et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most studies demonstrated that the IL-6 gene −572 G allele was associated with an increased risk of T2DM (Deng et al, 2004;Hamid et al, 2005;An et al, 2007;Koh et al, 2009;Tang et al, 2010;Wang et al, 2010). However, several other studies showed that there was no significant association between the IL-6 gene −572 C/G polymorphism and T2DM risk (Kitamura et al, 2002;Xiao et al, 2009;Zhang et al, 2011). A previous meta-analysis showed that the IL-6 gene -174 G/C polymorphism was not associated with T2DM risk (Qi et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Several epidemiological studies have reported the associations between several genetic variants of IL-6 and risk of T2DM, for instance, -174G/C, −572C/G, -597G/A and -1363G/T (Kitamura et al, 2002;Deng et al, 2004;Hamid et al, 2005;An et al, 2007;Chen et al, 2009;Koh et al, 2009;Xiao et al, 2009;Tang et al, 2010;Wang et al, 2010;Zhang et al, 2011). Of these studies, although the association between the IL-6 gene −572 C/G polymorphism and T2DM risk has been intensively studied, the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 After that,several studies found different results regarding the relationship between IL-6(-174) gene polymorphism and periodontal disease. Some of these studies did not find any association between IL-6(-174) gene polymorphism and CP, 12,13,14,15 however some others found associations. 16,17 Studies investigating the relationship between IL-6(-174) gene polymorphism and AgP are limited.…”
Section: Introductionmentioning
confidence: 99%
“…2 CP affects the periodontium, and although bacteria are essential for the disease initiation, bacteria number and type are not sufficient to explain the differences in their severity. 3 Besides the pathogenesis of chronic lesions is associated with the interaction among biofilm, host response and influences of secondary factors, genetic polymorphism may be determinant of certain immunological aspects of the disease. 4 Smoking is an important epidemiological factor associated with CP 5 as well as some systemic conditions such as diabetes and cardiovascular disease, especially hypertension.…”
Section: Introductionmentioning
confidence: 99%